2021
DOI: 10.1210/clinem/dgab412
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and White Matter Microstructure Development in Congenital Hypothyroidism and Familial Thyroid Disorders

Abstract: Context Children with congenital hypothyroidism (CH) are at risk for suboptimal neurodevelopment. Objectives To evaluate neurocognitive function and white matter microstructure in children with permanent or transient CH and to correlate these findings with disease severity. Design, participants and methods A retrospective and prospective observational study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Mean IQ was normal and comparable to controls however, there was a great variability in IQ values with a high percentage of CH patients having sub-optimal IQ (28.6%) and intellectual disability (10.7%). A significant impairment was detected in specific neurocognitive outcomes such as processing speed, visual attention, reading skills and arithmetic which correlated with white matter structure abnormalities ( 9 ). In this study the age at the beginning of treatment was quite variable (15.3 ± 7.9 days) as well as L-T4 starting dose (9.46 ± 2.28 µg/kg/day) and the mean TSH values (6.98 ± 4.68 µU/L) at the time of cognitive assessment was mildly elevated in some CH patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean IQ was normal and comparable to controls however, there was a great variability in IQ values with a high percentage of CH patients having sub-optimal IQ (28.6%) and intellectual disability (10.7%). A significant impairment was detected in specific neurocognitive outcomes such as processing speed, visual attention, reading skills and arithmetic which correlated with white matter structure abnormalities ( 9 ). In this study the age at the beginning of treatment was quite variable (15.3 ± 7.9 days) as well as L-T4 starting dose (9.46 ± 2.28 µg/kg/day) and the mean TSH values (6.98 ± 4.68 µU/L) at the time of cognitive assessment was mildly elevated in some CH patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of CH patients with subnormal IQ suggest that neurodevelopmental rescue should not be taken for granted even in the era of neonatal screening ( 27 ). Prenatal brain damage due to thyroid hormone insufficiency in utero , may not be completely prevented by trans-placental supply of maternal thyroxine and may not be completely reverted by postnatal treatment ( 9 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we could confirm white matter thinning in TH transporter deficient animals which is particularly present in the corpus callosum. A recent MRI study demonstrated that such white matter abnormalities in patients with permanent congenital hypothyroidism were associated with worse cognitive function [ 28 ]. Moreover, our structural MRI analysis revealed a prominent decrease of grey matter volume in Mct8/Oatp1c1 DKO mice within a large cluster covering subcortical striatal regions and prefrontal (OF, PL, IL, Cing, I) and sensorimotor cortical areas.…”
Section: Discussionmentioning
confidence: 99%
“…Even milder attenuation of TH actions in the CNS could pose a significant risk to neurodevelopment. For example, children with permanent congenital hypothyroidism were reported to have lower cognitive scores than those with transient congenital hypothyroidism and control subjects even if they received replacement therapy (39).…”
Section: Discussionmentioning
confidence: 99%